A Multidisciplinary Investigation Into the Eruptive Style, Processes, and Duration of a Cascades Back-Arc Tholeiitic Basalt: A Case Study of the Brushy Butte Flow Field, Northern California, United States - Downs, Drew T.; Champion, Duane E.; Clynne, Michael A.; Muffler, L. J. Patrick (Frontiers in Earth Science, 2021)
The Cascades back-arc in northern California is dominated by monogenetic tholeiitic basalts that erupted throughout the Pleistocene. Elucidating their eruptive history and processes is important for understanding potential future eruptions here. We focus on the well-exposed monogenetic volcano that emplaced the Brushy Butte flow field, which constructed a ∼150 m tall edifice, has flow lobes up to >10 km long, and in total covers ∼150 km2 with an eruptive volume of 3.5 km3. We use a multidisciplinary approach of field mapping, petrography, geochemistry, paleomagnetism, geochronology, and lidar imagery to unravel the eruptive history and processes that emplaced this flow field. Tholeiitic basalts in northern California have diverse surface morphology and vegetation cover but similar petrographic appearances, which makes them hard to distinguish in the field. Geochemistry and paleomagnetism offer an independent means of distinguishing tholeiitic basalts. Brushy Butte flow field lavas are similar in major-oxide and trace-element abundances but differ from adjacent tholeiitic basalts. This is also apparent in remanent magnetic directions. Additionally, paleomagnetism indicates that the flow field was emplaced during a geologically brief time interval (10–20 years), which 36Cl cosmogenic dating puts at 35.7 ± 1.7 ka. Lidar imagery shows that these flows erupted from at least 28 vents encompassing multiple scoria cones, spatter cones, and craters. Flows can be grouped into four pulses using stratigraphic position and volume. Pulse 1 is the most voluminous, comprising eight eruptions and ∼2.3 km3. Each subsequent pulse started rapidly but decayed quickly, and each successive pulse erupted less lava (i.e., 2.3 km3 for pulse 1, 0.6 km3 for pulse 2, 0.3 km3 for pulse 3, and 0.2 km3 for pulse 4). Many of these flows host well-established lava channels and levees (with channel breakouts) that lead to lava fans, with some flows hosting lava ponds. Similar flow features from tholeiitic eruptions elsewhere demonstrate that these morphologies generally occur over weeks, months, or longer (e.g., Puʻu ʻŌʻō eruption at K–llauea, Hawaiʻi). This multidisciplinary study shows the range of eruptive styles and durations of a Cascades back-arc eruption and illustrates how potential future tholeiitic eruptive activity in the western United States might progress.